HUBUNGAN KEBIASAAN MEROKOK TERHADAP SMOKER MELANOSIS PADA SISWA SMA HKBP SIDORAME MEDAN - Simbolon, Green Juninas; Sartini, Sartini; Fauziah, Ida (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2016)
This reseacrh was conducted to determine the relationship between smoking and oral melanosis. The samples were all of male students of Sidorame high school aged 15-17 years. Data were obtained by examining volunteerâs gum and asking them to fill in the questionners given. The result showed that there were strong relationship between smoking and melanosis (r = 0.887) furthermore the R value is 0.94 which concluded that smoking contribution smokers melanosis is 94%.